Measurement and correlation of fatigue and sleep quality in Parkinson’s disease: a cross sectional study - Gomes, Wildja de Lima; Silva, Laize Gabriele Castro; Silva, Neildja Maria da; Costa, Robison Carlos Silva; Cacho, Roberta de Oliveira; Lima, Núbia Maria Freire Vieira; Cacho, Ênio Walker Azevedo (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: Fatigue corresponds to a non-motor symptom of high prevalence in Parkinson’s disease (PD) affecting about one third of patients with the disease. This symptom negatively affects daily activities, contributing to the deterioration of the quality of life of these subjects. Objectives: To estimate fatigue in PD and to correlate with demographic characteristics, sleep, disease stage, motor function and daily activities. Methods: The sample consisted of patients with PD. The following measuring instruments were used for the study:Hoehn and Yahr scale, Fatigue Rating Scale, Unified Parkinson’s Disease Rating Scale, Parkinson’s Disease Sleep Scale. Results: This study highlights the high prevalence of fatigue in subjects with PD, and the screening and treatment of this symptom is extremely relevant in clinical practice. There were no significant correlations between fatigue and other variables analyzed. Conclusions: Most participants reported fatigue as a relevant problem, so it is important the use of instruments for fatigue screening in clinical practice and the need to develop therapies related to this symptom in the PD.